Development of Ball Dropper Media on Hitting Practices in Softball Games - Bangun, Sabaruddin Yunis; Arnas, Fachrul Rozy (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
This research aims to produce a medium for practicing (hitting) the game of Softball. The method used is research and development (R&D). Data collection techniques: (1) Observation, (2) Interview. The data analysis technique used descriptive statistics with a Likert scale. The population in this study was 30 people, 10 small-scale test athletes, and 20 large-scale athletes. The ball dropper media development was validated by 3 experts, 1 sports expert, 1 electrical expert, and 1 media expert. The percentage of validation is 92, %, 84%, and 88%. The results of the research of respondents from a small trial involving 10 people, showed that the ball dropper media showed a figure of 75.33% which means it is still in the feasible stage and still needs to be improved, followed by a large test involving 20 people, the percentage is 93.06%. This research concludes that the development of Ball dropper media as a media for hitting practice in softball games is considered very feasible to help practice hitting in softball games.